Opening Address: The Separation of Powers: An Exemplar of the Rule of Law - Dick Thornbaugh (Washington University Law Quarterly, 1990)
The doctrine of separation of powers is a basic tenet ofAmerican jurisprudence. This Symposium probes into its ongoing vitality in shaping contemporary legal and public policy issues. The following is a documentation of the Federalist Society Conference entitled "The Presidency and Congress: Constitutionally Separated and Shared Powers" held on January 19 and 20, 1990 at the Mayflower Hotel in Washington, D.C.